THERAPEUTIC FACTORS IN PSYCHODRAMA THERAPY APPROACH - Dony Darma Sagita; Neviyarni Neviyarni; Yeni Karneli; Netrawati Netrawati (Jurnal Neo Konseling, 2021)
Psychodrama is a form of human development by exploring, through dramatic action, problems, issues, ideas, dreams and the highest ideals of people, groups, systems and organizations. This approach is often used as a group model approach in guidance and counseling, where everyone in the group can be an agent in alleviation (therapeutic agent) between each other in the group. Psychodrama groups and self-help groups are designed with structure and dynamics. Various general factors in the implementation of the drama are the model factors or techniques used in the psychodrama counseling process, the client's expectations and expectations, the therapeutic relationship factor, and the client's extra therapy factor. A calm understanding of these factors will be a means of information for counselors in developing counseling skills, especially in building relationships with counseling using the psychodrama model